2022
DOI: 10.1111/bcp.15223
|View full text |Cite
|
Sign up to set email alerts
|

The negative impact of vitamin D on antipsychotic drug exposure may counteract its potential benefits in schizophrenia

Abstract: Aims Patients with schizophrenia frequently show insufficient vitamin D levels, which are associated with somatic comorbidity and may contribute to psychopathology. For many reasons, vitamin D supplementation may be indicated for this patient cohort. However, there is growing evidence for a vitamin D‐mediated increase of drug metabolism by induction of cytochrome P450 (CYP) 3A4. Hence, this study aimed to assess vitamin D's impact on both antipsychotic drug concentrations and psychopathology in a non‐intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Indeed, a previous study even revealed increased serum levels of both, aripiprazole and dehydroaripiprazole, following the application of the CYP3A4‐inhibitor itraconazole corresponding to an increased active moiety 19 . Accordingly, our own previous research suggested that serum concentrations of 25‐OH vitamin D, an inducer of CYP3A4, were negatively correlated with the active moiety of aripiprazole 42 . Therefore, we expect that a co‐treatment with duloxetine might also increase the active moiety of aripiprazole and dehydroaripiprazole.…”
Section: Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, a previous study even revealed increased serum levels of both, aripiprazole and dehydroaripiprazole, following the application of the CYP3A4‐inhibitor itraconazole corresponding to an increased active moiety 19 . Accordingly, our own previous research suggested that serum concentrations of 25‐OH vitamin D, an inducer of CYP3A4, were negatively correlated with the active moiety of aripiprazole 42 . Therefore, we expect that a co‐treatment with duloxetine might also increase the active moiety of aripiprazole and dehydroaripiprazole.…”
Section: Limitationsmentioning
confidence: 88%
“…19 Accordingly, our own previous research suggested that serum concentrations of 25-OH vitamin D, an inducer of CYP3A4, were negatively correlated with the active moiety of aripiprazole. 42 Therefore, we expect that a co-treatment with duloxetine might also increase the active moiety of aripiprazole and dehydroaripiprazole. Future studies should seek to confirm this hypothesis by investigating both, the parent compound and its active metabolite, in patients with or without co-treatment with duloxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the quantitative estimates of clozapine's impact on sertraline plasma concentrations have to be considered as rather uncertain. Another limitation is the non-normal (right-skewed) distribution of plasma levels requiring nonparametric statistical tests, which is however, a common finding related to TDM studies ( 46,47 ). As a further limitation, plasma concentrations of desmethylsertraline, the main metabolite of sertraline, were not available.…”
Section: Limitationsmentioning
confidence: 99%